2006
DOI: 10.1002/anie.200600408
|View full text |Cite
|
Sign up to set email alerts
|

In(OTf)3‐Catalyzed Tandem Nucleophilic Addition and Cyclization of ortho‐Alkynylarylaldimines to 1,2‐Dihydroisoquinolines

Abstract: Multitasking catalyst: 1,2‐Dihydroisoquinoline derivatives are prepared in good yields by an In(OTf)3‐catalyzed tandem annulation reaction. The catalyst activates both the imine and alkyne to the addition of various nucleophiles and the subsequent intramolecular cyclization (see picture; OTf=trifluoromethanesulfonate).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(26 citation statements)
references
References 71 publications
0
25
1
Order By: Relevance
“…The results are in sharp contrast to the nickel‐,4bd palladium‐,4eh and rhodium‐catalyzed4ik formation of isoquinolinium salts from o ‐halobenzaldimines and alkynes. The formation of indenamine II prompted us to explore the possibility for the application of this cobalt catalysis to the synthesis of indenoisoquinolinones.…”
Section: Resultscontrasting
confidence: 64%
“…The results are in sharp contrast to the nickel‐,4bd palladium‐,4eh and rhodium‐catalyzed4ik formation of isoquinolinium salts from o ‐halobenzaldimines and alkynes. The formation of indenamine II prompted us to explore the possibility for the application of this cobalt catalysis to the synthesis of indenoisoquinolinones.…”
Section: Resultscontrasting
confidence: 64%
“…[10][11][12][13][14][15][16][17] Among the various methods, the most common are functionalization of preformed isoquinoline core 10 and 6-endo-dig ring closure reactions of 2-(1-alkynyl) arene carboxaldehyde imines [11][12][13][14][15][16][17] (preformed or generated in situ from oalkynyl benzaldehydes and amines) in the presence of various pronucleophiles, either in the absence of a catalyst or in the presence of bond coordinating Lewis acid catalysts. [12][13][14][15][16] Especially, silver catalyzed ring closure reactions enjoyed more success. 12 However, these reactions, except few examples, 13 are mainly restricted to expensive second and third row transition metals (Ag,12 Pd,14 In, 15,16a Au 16 ).…”
mentioning
confidence: 99%
“…The optimization of reaction condition was carried out with respect to different Lewis acids, reaction temperatures and solvents. First, we screened different Lewis acids in 1,2-dichloroethane as solvent for nitro-Mannich reaction imine 1a at 80 °C (Table 1, entries 1, [11][12][13][14][15][16][17]. In the current transformation, the results showed that CoCl 2 and AgOTf , in contrast to the reaction timing, were competent catalysts to give good yields (Table 1, entries 1 & 13), whereas other Lewis acids (AgNO 3 , PdCl 2 , PdCl 2 (PPh 3 ) 2 ) were somewhat inferior (Table 1, entries14-16).…”
mentioning
confidence: 99%
“…Indeed, by switching to the less reactive 2-alkynyl-acetophenones as substrates their reaction with ammonia is not observed at all in the absence of a catalyst. By choosing as model system the reaction of 1-{2-[(4-methylphenyl)ethynyl]phenyl} ethanone 19a with ammonia, we tried some metal catalysts potentially able to promote both the imine formation and the intermolecular hydroamination step (Scheme 11) [36] [37], gold [38] and indium [39], in the intramolecular annulation reactions involving alkynes bearing a proximate nucleophile. As reported in Scheme 11, a catalytic amount of TiCl 4 gave rise to a complex mixture of unidentified products (Scheme 11, entry 1) whereas the less acidic complex TiCl 4 $2THF gave very poor result also after an extended reaction time (Scheme 11, entry 2).…”
Section: Resultsmentioning
confidence: 99%